2013
DOI: 10.1007/s00125-013-3021-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental history of type 2 diabetes, TCF7L2 variant and lower insulin secretion are associated with incident hypertension. Data from the DESIR and RISC cohorts

Abstract: Aims/hypothesis The relationship between insulin secretion and the incidence of hypertension has not been well characterised. We hypothesised that both a parental history of diabetes and TCF7L2 rs7903146 polymorphism, which increases susceptibility to diabetes because of impaired beta cell function, are associated with incident hypertension. In a separate cohort, we assessed whether low insulin secretion is related to incident hypertension. Methods Nine year incident hypertension was studied in 2,391 normotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…On the other hand, the pleotropic effects of T allele on the factors promoting MetS or preventing MetS could partly explain the negative findings in previous studies [ 14 , 61 , 62 , 63 ]. In addition, a study reported that the T allele was the risk factor for incident hypertension [ 64 ] or increased TG level in elderly population [ 22 ], which was inconsistent with the present findings. However, the inconsistency could be partly explained by the different study design and population, as both the phenotypes were closely connection to blood glucose.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the pleotropic effects of T allele on the factors promoting MetS or preventing MetS could partly explain the negative findings in previous studies [ 14 , 61 , 62 , 63 ]. In addition, a study reported that the T allele was the risk factor for incident hypertension [ 64 ] or increased TG level in elderly population [ 22 ], which was inconsistent with the present findings. However, the inconsistency could be partly explained by the different study design and population, as both the phenotypes were closely connection to blood glucose.…”
Section: Discussioncontrasting
confidence: 99%
“…Taken as a whole, it seems unlikely that our results may be explained solely by the effect of reduced insulin secretion on inflammation. We described in the RISC study a link between insulin secretion and the risk of development of hypertension, which is another potential confounder in the current analysis [29].…”
Section: Discussionmentioning
confidence: 98%
“…It is well documented that blood pressure is an important AF risk factor, including high normal blood pressure [ 35 - 38 ]. Furthermore, it has recently also been shown that low insulin secretion is associated with increased incidence of hypertension in studies of families at genetic risk of type 2 diabetes [ 39 ]. It is therefore possible that different actions of insulin on the vasculature and hemodynamic regulation, and thereby the blood pressure levels, could contribute to explain the results of the present study.…”
Section: Discussionmentioning
confidence: 99%